The predictive score for early-onset neonatal sepsis - Selimovic, Amela; Skokic, Fahrija; Bazardzanovic, Mustafa; Selimovic, Zijad (The Turkish Journal of Pediatrics, 2010)
The aim of the present study was to analyze complete blood count (CBC) and C-reactive protein (CRP) levels to create the predictive score for diagnosis of early-onset neonatal sepsis (EONS). All neonates treated for suspected EONS between January 2004 and December 2006 were evaluated from their case record. A diagnosis of EONS was made if either clinical findings consistent with sepsis developed within 72 hours of life, or if positive cultures were obtained. Evaluations for EONS were preformed in 341 neonates, and 199/341 (58.4%) developed EONS. Total white blood count, immature/total ratio, immature/ mature ratio, and CRP levels were found to be independent predictors of EONS, and the predictive score for EONS was created. An increase in the predictive score for EONS was directly correlated with possibility of EONS. Receiver operating characteristic (ROC) curve analysis determined a cut-off value of a predictive score for EONS > 0.503, with sensitivity of 73% and specificity of 89%. Correct prediction of EONS was found in 78% of all neonates, 80% for positive and 75% for negative outcome (p < 0.0001). In conclusion, for its high sensitivity and prediction rates, the predictive score for EONS is useful in diagnostic evaluation of neonates suspected for EONS.